Combining Diuretic Response and Hemoconcentration to Predict Rehospitalization After Admission for Acute Heart Failure. (June 2016) - ter Maaten, Jozine M.; Valente, Mattia A.E.; Damman, Kevin; Cleland, John G.; Givertz, Michael M.; Metra, Marco; O'Connor, Christopher M.; Teerlink, John R.; Ponikowski, Piotr; Bloomfield, Daniel M.; Cotter, Gadi; Davison, Beth; et al.
Abstract : Background—: Both diuretic response and hemoconcentration are indicators of decongestion and have individually been found to predict rehospitalization after admission for acute heart failure (HF). This study examines the value of combining diuretic response and hemoconcentration to better predict patients at low risk for rehospitalization after admission for acute HF. Methods and Results—: Diuretic response (defined as weight change per 40 mg of furosemide on day 4 after admission) and hemoconcentration (change in hemoglobin at discharge or day 7) were tested both individually and combined to predict the risk of HF and cardiovascular rehospitalization 60 days after hospitalization for acute HF. Analyses were performed in 1180 patients enrolled in the Placebo-Controlled Randomized Study of the Selective Adenosine Receptor Antagonist Rolofylline for Patients Hospitalized With Acute Decompensated Heart Failure and Volume Overload to Assess Treatment Effect on Congestion and Renal Function (PROTECT) trial and validated in 1776 patients enrolled in the Efficacy of Vasopressin Antagonism in Heart Failure Outcome Study With Tolvaptan (EVEREST) trial. Poor diuretic response was associated with low systolic blood pressure, high blood urea nitrogen, and history of coronary revascularization in both data sets (all P <0.05). Hemoconcentration was mainly associated with better renal function ( P <0.05). Patients who displayed both favorable diuretic response and hemoconcentration had a markedly lower risk of rehospitalization for HF in PROTECT (multivariable HR, 0.41; 95% CI, 0.24 to 0.70; P <0.001) compared with all other patients. This finding was confirmed in EVEREST (multivariable HR, 0.52; 95% CI, 0.33 to 0.82; P =0.004) for patients with favorable diuretic response and hemoconcentration compared with all other patients. Conclusions—: Combining 2 indicators of decongestion, hemoconcentration and diuretic response improves risk prediction for early rehospitalization after an admission for acute HF and may provide clinicians with an easily accessible tool to identify low-risk patients. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifiers: NCT00354458 and NCT00071331. Abstract : Supplemental Digital Content is available in the text.